THE INFLUENCE OF KNOWLEDGE SHARING BEHAVIOR, COMPENSATION, MOTIVATION, ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE - Nur Alifah Rosidatun Nuha; Nova Nursafitri; Wina Nabila; Devi Nopianti (JABI (Journal of Accounting and Business Issues), 2023)
Employee performance is the result of work in quality and quantity achieved by an employee in carrying out their duties in accordance with the responsibilities given. Several factors are believed to have an impact on employee performance. However, in this study the factors that need to be examined for their influence on employee performance are knowledge sharing behavior, compensation, motivation and organizational culture. The method used in this study is quantitative. The results of the study state that the variables of knowledge-sharing behavior, compensation, motivation and organizational culture affect employee performance because it is based on the Adjusted R Square (R2) value of 0.661 which indicates that the influence of the four independent variables on the dependent variable is 66 %, and the remaining 34% comes from several other factors not examined in this study. These results conclude that the fifth hypothesis in this study is accepted which states that there is an influence of knowledge sharing behavior, compensation, motivation and organizational culture on employee performance.